2015
DOI: 10.1007/s11102-015-0659-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of AIP mutations in a series of Turkish acromegalic patients: are synonymous AIP mutations relevant?

Abstract: The prevalence of AIP(mut) in Turkish patients was found to be 1 % in sporadic acromegaly in the present study. This ratio increases when younger age groups are taken into account 6 % among patients <30 years of age at the time of diagnosis of acromegaly. The clinical features of acromegaly, such as having large and invasive tumours, may be affected by the presence of synonymous AIP(mut).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the FIPA setting, AIP pathogenic variants are demonstrated in about 20% of families, while in cohorts of unselected apparently sporadic pituitary adenomas AIP pathogenic variants are rarely found -in less than 4% (11,84). However, in young adults (diagnosed < 30 years of age) with apparently sporadic adenomas (mostly macroadenomas), the prevalence of AIP pathogenic variants was higher, ranging between 1.6 and 13% (85,86,87,88,89,90,91,92,93). Further decreasing the age of diagnosis (pediatric/ adolescent patients <18 year/old) increases the frequency of AIP pathogenic variants to 11-25% (85,87,94,95,96,97,98).…”
Section: Aip Mutations In Fipa and Sporadic Pituitary Adenomasmentioning
confidence: 99%
“…In the FIPA setting, AIP pathogenic variants are demonstrated in about 20% of families, while in cohorts of unselected apparently sporadic pituitary adenomas AIP pathogenic variants are rarely found -in less than 4% (11,84). However, in young adults (diagnosed < 30 years of age) with apparently sporadic adenomas (mostly macroadenomas), the prevalence of AIP pathogenic variants was higher, ranging between 1.6 and 13% (85,86,87,88,89,90,91,92,93). Further decreasing the age of diagnosis (pediatric/ adolescent patients <18 year/old) increases the frequency of AIP pathogenic variants to 11-25% (85,87,94,95,96,97,98).…”
Section: Aip Mutations In Fipa and Sporadic Pituitary Adenomasmentioning
confidence: 99%
“…A pan-European collaboration [ 12 ] analysed a cohort of 163 patients diagnosed with sporadic pituitary macroadenomas before the age of 30 years and reported an 11.7% (19/163) prevalence of AIP mutations. Likewise, other studies carried out in Turkey [ 20 ], Mexico [ 21 ], and Spain [ 22 ], in patients under 30 years, reported prevalences of AIP mutations of 9% (1/11), 7% (5/55), and 6% (9/148), respectively. In contrast, our study showed that only 3.4% (4/118) of Portuguese patients diagnosed under the age of 30 years had AIP mutations.…”
Section: Discussionmentioning
confidence: 61%
“…Disease onset is typically at a younger age in AIP gene variant human acromegalics compared to other causes of acromegaly [10]. AIP-variant acromegaly has also been identified in patients with non-familial human acromegaly [11,12].…”
Section: Introductionmentioning
confidence: 99%